Analisis Kondisi Resapan Air Dengan Menggunakan Sistem Informasi Geografis di Kabupaten Gunungkidul - Fahmi, Hamzah Haz, Ir. Taryono, M.Si, Agus Anggoro Sigit, S.Si., M.Sc (2016)
Gunung Kidul Regency is one of regencies in Yogyakarta Special Region, whose territory consists largely of karst topography, known as regional drought in the dry season. The general objective of this research was to analyze water recharge condition in the study area and analyze the factors that cause droughts that often occur in the study area. This study aims to 1) Identify zone of the condition of water catchment in the study area, 2) to analyze the dominant factors that affect the ability of infiltration in the area of research. The method used in this research is survey method (Stratified Sampling) and overlay. The parameters used is rock type, slope, soil type, vegetation density, precipitation and land use. Rock type, slope, soil type, vegetation density, rainfall parameters affect the ability of infiltration. Land use filters ability to function as an infiltration. Compilation or a combination of the ability of infiltration by land use have resulted in water recharge condition of research. The results of Geographic Information Systems (GIS) analysis produces four classes of water infiltration conditions in the study area, which consists of a good, normal naturally, began a critical and rather critical. Administratively, Shareable good condition of water recharge mostly in the District Patuk, Nglipar, Ngawen, Semin, Playen, Wonosari, Karangmojo. As for rather critical conditions of water recharge covers a fraction District of Purwosari, Bake, Paliyan, Saptosari, Wonosari, Tanjungsari, Tepus, Girisubo, Semanu, Ponjong, Karangmojo, Playen, Patuk, Gedangsari, Nglipar, Ngawen and Semin. The results of GIS analysis showed, generally rock type is the dominant factor affecting the ability of infiltration in the area of research. The dominant factor causing low infiltration capability in the research area is soil type parameter's.